Assessment of HEMA and TEGDMA induced DNA damage by multiple genotoxicological endpoints in human lymphocytes. Issue 8 (August 2015) - Ginzkey, Christian; Zinnitsch, Sabrina; Steussloff, Gudrun; Koehler, Christian; Hackenberg, Stephan; Hagen, Rudolf; Kleinsasser, Norbert H.; Froelich, Katrin
Highlights Human lymphocytes were exposed to HEMA and TEGDMA for 24 h. Cytotoxic effects were measured only in TEGDMA (100 μM) treated cells. Genotoxic effects were detected in the comet assay at the highest concentrations. No increase in the micronucleus frequency or an arrest of the cell cycle was shown. Chromosome aberrations and SCEs were recorded at lowest concentrations tested.